Я должна рассказать: повести - Рольникайте Мария Григорьевна (Повести ленинградских писателей, 1990)
Экземпляры: аб. (1990) / Инвентарный номер: 30938 / Цена: / Сис.шифр: 84(2Рос=Евр)6-4 / Авт.знак: Р 68 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Евр)6-44